Síntese e caracterização de nanocristais de ZnO suportados e não suportados em diatomita e aplicação fotocatalítica - Santos, Yane Honorato (2017)
Currently there are many studies involving Nanocrystals (NC) incorporated into different types of matrices, including, matrices with porous surface. However, little information is known about the incorporation of NC in Diatomite matrix, and there is a lack of studies on the use of this material. In this context, zinc oxide (ZnO) semiconductor nanoparticles were prepared using two sol-gel methods, microwave and autoclave, at 100 ºC and 180 ºC, respectively. The nanocrystals of ZnO obtained by microwaves were incorporated into a matrix of diatomite (DE) in natura and modified. The modifiers used were APTES (3- aminopropyltriethoxysilane) and MPTS (3-Mercaptopropyltrimetoxysilane) for the study. The material DE/ ZnO, in which ZnO was synthesized with mercaptoethanol (ZnO: ME), was applied for the degradation of Methylene Blue (AM) dye, while ZnO, synthesized with diethyleneglycol (ZnO: DEG), was used for degradation of Rhodamine 6G dye (R6G) by photocatalysis. The results of UV-vis and FTIR spectra show that synthesis carried out by heating under adsorption method is more efficient for the incorporation of ZnO in Diatomite matrix. The FTIR spectra showed that the use of modifiers had no significant influence on the structure. According to the UV-Vis spectra, the DE / ZnO material was successful for application to AM photocatalysis and follows a pseudo-first order kinetics. The ZnO:DEG material used for degradation of R6G obtained higher efficiency due to the wide absorption in the UV-Vis of the photocatalyst material.